1972
DOI: 10.1159/000466557
|View full text |Cite
|
Sign up to set email alerts
|

Anti-N-Like Antibodies in the Sera of Patients Undergoing Chronic Hemodialysis

Abstract: Within the last two years, 12 examples of red cell antibody with apparent anti- N specificity have been found in the sera of 416 prospective kidney transplant recipients maintained on chronic hemodialysis. Eight of the 12 patients were N-positive, three of them in the homozygous state. Serial samples from these patients were tested against M, MN and N cells of compatible ABO types, and in 10 of the 12 cases against the patients’ own red cells. Anti-N-like antibody was detected only after many months of chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1974
1974
1978
1978

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…The results demonstrate a high incidence of a specific cold agglutinin cross-reacting with anti-N in haemodialysis patients. In accordance with the results of Howell and Perkins [7], blood transfusions and/or pregnancies as a cause for isoimmunisation could be excluded. The development of the antibody was dependent on the duration of the regular haemodialysis treatment.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The results demonstrate a high incidence of a specific cold agglutinin cross-reacting with anti-N in haemodialysis patients. In accordance with the results of Howell and Perkins [7], blood transfusions and/or pregnancies as a cause for isoimmunisation could be excluded. The development of the antibody was dependent on the duration of the regular haemodialysis treatment.…”
Section: Discussionsupporting
confidence: 62%
“…During the first 6 months of treatment we never found a patient who was anti-N-like positive. Howell and Perkins [ 7 ] discussed (a) the use of cellulose membranes for dialysis, (b) the reuse of the dialyser and (c) the use of formaldehyde as a sterilant as possible factors involved in the formation of the anti-N-like antibody. As all patients investigated in our study were dialysed on cellulose membranes (CuprophaneB) and the reuse per se had no influence on the frequency of positive antibody titers, these two factors can be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One serum (WAL) was passed through a Sephadex column and the IgG and IgM fractions tested separately for immunofluorescent activity. (2,4], sera from 26 patients undergoing dialysis were screened for red cell antibodies. The patients comprised 8 who had resumed dialysis following kidney transplant rejection and 18 who had not been transplanted.…”
Section: Methodsmentioning
confidence: 99%
“…Similar cases were r e p o r t e d by G r e e n w a l t et a1. 2 and by Moores et al 5 Howell et al 3 have found anti-N-like antibodies in several patients m a i n t a i n e d on chronic hemodialysis. There was no evidence of clinical hemolysis in any of these reports.…”
mentioning
confidence: 96%